Fluid Flow and Heat Transfer in Rotating Porous Media - Vadasz, Peter (SpringerBriefs in Thermal Engineering and Applied Science,, 2016)
This Book concentrates the available knowledge on rotating fluid flow and heat transfer in porous media in one single reference. Dr. Vadasz develops the fundamental theory of rotating flow and heat transfer in porous media and introduces systematic classification and identification of the relevant problems. An initial distinction between rotating flows in isothermal heterogeneous porous systems and natural convection in homogeneous non-‐isothermal porous systems provides the two major classes of problems to be considered. A few examples of solutions to selected problems are presented, highlighting the significant impact of rotation on the flow in porous media.